Perbandingan Massa Otot Lengan Dominan dan Tidak Dominan dengan Latihan Beban - Castendo, Cynthia C.; Pangemanan, Damajanty H.C.; Engka, Joice N.A. (Universitas Sam Ratulangi, 2020)
Abstract: Dominant arms are the most frequently used in activity. Weight training can influence the increase in muscle strength that automatically increases muscle mass on both dominant and non dominant arms. The study aims to determine the comparison between dominant and non dominant arms muscle mass with weight training. This research uses a field experiment study with one group pre and post-test design for 8 weeks on 37 male college students with right dominant arm and 5 male college students with left dominant arm. Subjects were weight trained using dumbbells. Muscle mass were measured on bicep-triceps muscles using a tape measure (cm) to measure upper arm circumference on each subjects prior and after training. Statistical test was done using the test of normality (Shapiro Wilk), paired sample t-test and Wilcoxon Signed Rank Test. Results of the paired sample t-test obtained p value = 0.00 (right and left upper arm circumference) on right dominant arm subjects and Wilcoxon Signed Rank test obtained p value = 0,042 (left upper arm circumference) and p value = 0,043 (right upper arm circumference) on left dominant arm subjects. Based on both test results there was a difference in muscle mass prior and after training although there were no significant differences in muscle mass between dominant and non dominant arms. In conclusion, there were no differences in muscle mass between dominant and non dominant arms with weight training.Keywords: weight training, dominant and non dominant arms, muscle mass Abstrak: Lengan dominan merupakan lengan yang paling sering digunakan dalam beraktivitas. Latihan beban dapat memberikan pengaruh pada pertambahan kekuatan otot yang secara otomatis meningkatkan massa otot pada kedua lengan dominan maupun tidak dominan. Penelitian ini bertujuan untuk menentukan perbandingan massa otot lengan dominan dan tidak dominan dengan latihan beban. Penelitian menggunakan penelitian eksperimental lapangan dengan rancangan one group pre and post-test design selama 8 minggu pada 37 mahasiswa laki-laki dominan kanan dan 5 mahasiswa laki-laki dominan kiri. Subjek diberi latihan beban dengan menggunakan dumbbell. Massa otot diukur pada otot bisep-trisep menggunakan alat ukur meteran (cm) untuk mengukur lingkar lengan atas (lila) tiap subjek sebelum dan sesudah latihan. Uji statistik menggunakan uji normalitas (shapiro wilk), uji t berpasangan dan uji Wilcoxon Signed Rank Test. Hasil uji t berpasangan didapatkan nilai p=0,00 (lila kanan dan kiri) pada subjek penelitian dominan kanan dan uji Wilcoxon Signed Rank Test didapatkan nilai p=0,042 (lila kiri) serta p=0,043 (lila kanan) pada subjek penelitian dominan kiri. Berdasarkan kedua uji didapatkan perbedaan massa otot sebelum dan sesudah latihan tetapi tidak ada perbedaan signifikan antara massa otot lengan dominan dan tidak dominan. Simpulan penelitian ini ialah tidak ada perbedaan massa otot lengan dominan dan tidak dominan dengan latihan beban.Kata Kunci: latihan beban, lengan dominan dan tidak dominan, massa otot